Lysosomal, genetic and chromosomal damage in haemocytes of the freshwater bivalve (Unio pictorum) exposed to polluted sediments from the River Cecina (Italy). Issue 6 (3rd July 2017) - Guidi, Patrizia; Bernardeschi, Margherita; Scarcelli, Vittoria; Cantafora, Emanuela; Benedetti, Maura; Falleni, Alessandra; Frenzilli, Giada
ABSTRACT: The response to chemical disturbance of an Italian river (Cecina River) characterised by high levels of trace metals was assessed in the sentinel species freshwater painter's mussel ( Unio pictorum ). We exposed U. pictorum in the laboratory to metal, metalloid and other trace element polluted river sediments in order to evaluate genetic and cellular biomarkers. Bivalves exposed to sediments taken from all the impacted sites of the river basin exhibited a significant impairment at the DNA, chromosomal and lysosomal levels. The lysosomal membrane stability of circulating haemocytes, assessed by the Neutral Red Retention Time, was found to be higher in specimens from Lake Maggiore and Berignone, while exhibited a significant decrease in specimens exposed to Ponteginori sediments. An increase of DNA migration in specimens exposed to the two contaminated sites in comparison with controls was found. Moreover, higher micronucleated haemocytes frequencies were observed in bivalves exposed to sediments collected at Possera 1 site. This study suggested that biomarkers evaluating cellular impairment, genetic and chromosomal damages, are highly sensitive and suitably applied to laboratory experiments. The painter's mussel was confirmed to be an appropriate sentinel species for quality assessment in metal-contaminated freshwater environments.